Comprehensive evaluation of time-varied outcomes for invasive and conservative strategies in patients with NSTE-ACS: a meta-analysis of randomized controlled trials - Zhao, Yi-Jing; Sun, Yangyang; Wang, Fan; Cai, Yuan-Yuan; Alolga, Raphael N.; Qi, Lian-Wen; Xiao, Pingxi (Frontiers in Cardiovascular Medicine, 2023)
Background: Results from randomized controlled trials (RCTs) and meta-analyses comparing invasive and conservative strategies in patients with NSTE-ACS are highly debatable. We systematically evaluate the efficacy of invasive and conservative strategies in non-ST-elevation acute coronary syndrome (NSTE-ACS) based on time-varied outcomes. Methods: The RCTs for the invasive versus conservative strategies were identified by searching PubMed, Cochrane Central Register of Controlled Trials, Embase and ClinicalTrials.gov. Trials data for studies that had a minimum of a 30-day follow-up time were included. We categorized the follow-up into six varied periods: ≤ 6 months, 1 year, 2 years, 3 years, 5 years, and ≥ 10 years. The time-varied outcomes were major adverse cardiovascular event (MACE), death, myocardial infarction (MI), rehospitalization, cardiovascular death, bleeding, in-hospital death, and in-hospital bleeding. RRs and 95% CIs were calculated. The random effects model was used. Results: We included 30 articles of 17 RCTs involving 12,331 participants in this meta-analysis.We found that invasive strategy did not provide appreciable benefit for NSTE-ACS in terms of MACE, death, and cardiovascular death at all time points compared with conservative strategy.Although there was a risk reduction in MI within 6 months (RR 0•80, 95%CI 0•68-0•94) for invasive strategy, no significant differences were found in other periods. The invasive strategy did reduce rehospitalization within 6 months (0•69, 0•52-0•90), 1 year (0•73, 0•63-0•86) and 2 years (0•77, 0•60-1•00). Of note, increased risk was observed for invasive strategy in bleeding within 6 months (1•80, 1•28-2•54) and in-hospital bleeding (2•17, 1•52-3•10). In subgroups stratified by high-risk features, the invasive strategy decreased MACE for patients ≥ 65 years within 6 months (0•68, 0•58-0•78) and 1 year (0•75, 0•62-0•91), and showed benefit for men within 6 months (0•78, 0•61-0•99). In other subgroups stratified according to diabetes, STsegment deviation and troponin levels, no significant differences were observed between the two strategies. Conclusions: An invasive strategy is superior to a conservative strategy in the reduction of early events for MI and rehospitalizations, but the invasive strategy appears not to improve prognosis in long-term outcomes for patients with NSTE-ACS.